“I Made It Work”: How Using a Self-Assembled Product Increases Task Performance - Sören Köcher; Keith Wilcox (Journal of Consumer Psychology, 2021)
Although it is well established that consumers have an increased valuation for self-assembled products, less is known about how using such products influences objective consumption outcomes. Across three experiments, the current research demonstrates that consumers perform better on tasks when they use a product they have self-assembled—as opposed to an identical but ready-to-use product. We show that this effect results from an increase in self-efficacy and rule out possible alternative accounts (i.e., product efficacy beliefs, performance motivation, feelings of psychological ownership, and product liking). In addition, we demonstrate that the self-assembly effect emerges only when consumers actually use the self-assembled product, is robust when product assembly requires different amounts of time and effort, and is not merely the result of a question-behavior effect. Theoretical contributions and opportunities for future research are discussed.
Keywords: 650; Task performance; Self-efficacy; Product assembly